Aprendizaje de estudiantes de secundaria sobre la naturaleza de la ciencia mediante el caso histórico de semmelweis Y la fiebre puerperal - Aragón-Méndez, María del Mar; García-Carmona, Antonio; Acevedo-Díaz, José Antonio (Revista Científica, 2016)
This paper presents the findings from the assessment of an activity for learning some nature of science (NOS) aspects using as context the historical case of Semmelweis’ research on childbed fever. The activity is intended for 15-16-year-old students and it was performed from an explicit and reflective approach. A rubric was employed to assess students’ learning, which was applied using a method of inter-rate analysis. Also, the teacher’s diary was used as a complementary tool of assessment. Globally, the findings show students’ progression in understanding the aspects of NOS addressed. The students attained a moderate level of understanding in relation to epistemic aspects, but their levels of understanding were higher regarding the non-epistemic. Therefore, the pedagogical potential of the activity for learning on NOS is evidenced. Finally, some educational implications of the experience are proposed.